A simple titrimetric method for the determination of osmium(IV) in chloride standard solutions and intermetallic alloys - Vrublevska, T.; Rydchuk, M.; Bonishko, O.; Mykhalyna, G. (Фізико-хімічна механіка матеріалів, 2010)
A new method for the standardization of osmium(IV) from chloride aqueous solutions by means of iodometric titration with visual (using starch as indicator) and potentiometric indicating of titration end point has been elaborated. This simple and rapid method is based on Os(IV) interaction with the excess of iodide-ions in sulphuric acid media and on the titration of liberated iodine with the standardized solution of sodium thiosulfate. The method was approved during the determination of milligram quantities of osmium(IV) in standard solution and intermetallic alloys. Relative standard deviations (RSDs) did not exceed 1.5 %. Розроблено нову методику стандартизації хлоридних водних розчинів осмію(IV) йодометричним титруванням з візуальною (за допомогою крохмалю) та потенціометричною фіксацією кінцевої точки титрування. Ця проста і експресна методика базується на взаємодії Os(IV) з надлишком йодид-іонів у сульфатнокислому середовищі та титруванні виділеного йоду стандартизованим розчином тіосульфату натрію. Методику апробовано під час визначення міліграмових кількостей осмію(IV) у стандартних розчинах та інтерметалічних сплавах. Похибка не перевищувала 1,5%. Разработана новая методика стандартизации хлоридних водных растворов осмия(IV) иодометрическим титрованием с визуальной (с помощью крахмала) и потенциометрической фиксацией конечной точки титрования. Эта простая и экспрессная методика основана на взаимодействии Os(IV) с избытком иодид-ионов в сернокислой среде и титровании выделенного иода стандартизированным раствором тиосульфата натрия. Методику апробировано при определении миллиграммових количеств осмия(IV) в стандартных растворах и интерметаллических сплавах. Погрешность не превышала 1,5%.